Effects of Wax Coating on the Surface Quality of EPS Patterns for Solid Mould Investment Casting - Guler, Kerem Altug (CARL HANSER VERLAG, 2013)
Expandable polystyrene (EPS) foam has been a well-known pattern material for a long time in the investment casting process, however it always suffers from insufficient surface finish compared to wax patterns. In this study, EPS foam patterns were coated with waxes and the effects of such coating on the surface quality were investigated. Cubic shaped EPS patterns were coated with liquid ordinary candle wax (c-wax) and commercial pattern wax (p-wax). These patterns and an uncoated pattern were used to prepare plaster bonded solid investment casting moulds and a A319 aluminium alloy was casted into these moulds. Average surface roughness (Ra) of the patterns, moulds internal surfaces and cast parts were measured, cross sections of the coated patterns were investigated by optical microscopy and the coating thicknesses were measured with an image analyser. As an obvious result, wax coating significantly increases the surface quality and the p-wax creates smoother, while the c-wax creates more uniform coating films.
Keywords: Materials Science